Variation in ocean conditions affects chick growth, trophic ecology, and foraging range in Cape Verde Shearwater. (21st February 2018) - Ramos, Jaime A.; Rodrigues, Isabel; Melo, Tommy; Geraldes, Pedro; Paiva, Vitor H.
Abstract: Varying environmental conditions have a strong effect on the reproductive- and feeding-ecology measures of seabirds. We assessed how annual variation in the isotopic niche of foraging adults during the chick-rearing season, the size of at-sea foraging areas, and oceanographic characteristics influenced annual variation in linear growth rate and asymptotic mass of Cape Verde Shearwater ( Calonectris edwardsii ) chicks in 2013–2015. We also examined correlations between chick growth measures and chlorophyll a concentration (CHL) and sea surface temperature anomaly (SSTa) within the foraging areas of their parents in 2014 and 2015. Oceanographic conditions were unfavorable in 2013, with lower CHL and higher SSTa. In 2013 chicks had a lower asymptotic mass, and foraging adults had a wider isotopic niche, larger at-sea home range, and larger foraging areas, suggesting that poor foraging conditions forced parents to search for prey over a larger area. We did not detect significant relationships between CHL and SSTa within the adults' foraging range or chick growth measures in 2014 and 2015. The relationship between oceanographic conditions and breeding success in Cape Verde Shearwater and other tropical seabirds should be examined further across years with varying environmental conditions, and with GPS tags that monitor the entire nesting period.